Managing of Spring Barley Fungal Spot Blotch Disease Under the Basic, Intensive and High Intensive Cultivation Technologies in Moscow - Sediqi, Abdul Nasir; Saeedi, Ghani Dad; Nikzad, Kazem; Nasrat, Nasir Ahmad (Journal for Research in Applied Sciences and Biotechnology, 2024)
Spring barley (Hordeum vulgare L.), is one of the fourth largest grain in the world but insects, weeds and diseases agents lead to crop losses and declination of incomes. Fungal diseases cause serious losses in spring barley prompting the need to find an effective strategy of control. In the quest to find a suitable strategy, application of three treatments, high intensive, intensive and basic. In 2020, varieties (factor A) of spring barley were grown: Elf, Yaromir and Vladimir, which were placed in experimental variants that differed in the level of application of mineral fertilizers and plant protection products-basic, intensive and high-intensity technologies (factor B). We studied seeding rates - 4, 5 and 6 million germinating grains per hectare. The technology used modern drugs from Keminova), involving the application of fungicides and fertilizer compounds were evaluated for the control of fore critical fungal disease such as Spot blotch (Bipolaris sorokiniana) disease spring barley varieties Elf, Yaromir and Vladimir. The outcome of the experiment shows that the basic technology treatment with fertilizers and mixture of herbicide, insecticide and fungicides compounds were the most effective strategy in controlling the fungal Spot blotch disease, weeds, insects and increasing the yields of three varieties Elf, Yaromir and Vladimir, which was used only in autumn spring defense is forecast. The yield in the intensive treatments was close in value, respectively, 10.47 T/ha, 10.27 T/ha and 9.15 T/ha which is higher by 27%, 21% and 33 % compared to basic treatments. The outcome was reflected in the segments of the grain yield, with the end goal that the weight and mass of 1000 part were improved in three therapies contrasted with fundamental since the high escalated application was more compelling in such manner. The 3 treatments such as, high intensive, intensive and basic technologies (factor B) on three spring barley varieties (Factor-A), to control fungal disease in three replicated factorial in randomized complete block design (RCBD) containing net plot size i.e. 2 m × 5 m (10 m2). The experiments were fulfillment during the 2020 years and impact of the 3 diverse mixed protection basic, intensive and high intensive technologies were tried.